A spatial map of antennal-expressed ionotropic receptors in the malaria mosquito - Joshua I. Raji; Joanna K. Konopka; Christopher J. Potter (Cell Reports, 2023)
Summary: The mosquito’s antenna represents its main olfactory appendage for detecting volatile chemical cues from the environment. Whole-mount fluorescence in situ hybridization of ionotropic receptors (IRs) expressed in the antennae reveals that the antenna might be divisible into proximal and distal functional domains. The number of IR-positive cells appear stereotyped within each antennal segment (flagellomere). Highly expressed odor-tuning IRs exhibit distinct co-localization patterns with the IR coreceptors Ir8a, Ir25a, and Ir76b that might predict their functional properties. Genetic knockin and in vivo functional imaging of IR41c-expressing neurons indicate both odor-induced activation and inhibition in response to select amine compounds. Targeted mutagenesis of IR41c does not abolish behavioral responses to the amine compounds. Our study provides a comprehensive map of IR-expressing neurons in the main olfactory appendage of mosquitoes. These findings show organizing principles of Anopheles IR-expressing neurons, which might underlie their functional contribution to the detection of behaviorally relevant odors.